Novel idebenone analogs block Shc’s access to insulin receptor to improve insulin sensitivity - Hui, ChunKiu; Tomilov, Alexey; Garcia, Chase; Jiang, XiaoSong; Fash, David M.; Khdour, Omar M.; Rosso, Cristian; Filippini, Giacomo; Prato, Maurizio; Graham, James; Hecht, Sidney; Havel, Peter; et al. (Biomedicine & pharmacotherapy, 2020)
[Display omitted] •Idebenone drug engagement of p52Shc protein regulates insulin sensitivity.•Analogs of idebenone engage p52Shc and insulin-sensitizer differentially.•One analog is a more potent insulin sensitizer than idebenone itself.•Idebenone metabolites engage p52Shc and insulin sensitize. There has been little innovation in identifying novel insulin sensitizers. Metformin, developed in the 1920s, is still used first for most Type 2 diabetes patients. Mice with genetic reduction of p52Shc protein have improved insulin sensitivity and glucose tolerance. By high-throughput screening, idebenone was isolated as the first small molecule 'Shc Blocker'. Idebenone blocks p52Shc's access to Insulin Receptor to increase insulin sensitivity. In this work the avidity of 34 novel idebenone analogs and 3 metabolites to bind p52Shc, and to block the interaction of p52Shc with the Insulin receptor was tested. Our hypothesis was that if an idebenone analog bound and blocked p52Shc's access to insulin receptor better than idebenone, it should be a more effective insulin sensitizing agent than idebenone itself. Of 34 analogs tested, only 2 both bound p52Shc more tightly and/or blocked the p52Shc-Insulin Receptor interaction more effectively than idebenone. Of those 2 only idebenone analog #11 was a superior insulin sensitizer to idebenone. Also, the long-lasting insulin-sensitizing potency of idebenone in rodents over many hours had been puzzling, as the parent molecule degrades to metabolites within 1 h. We observed that two of the idebenone’s three metabolites are insulin sensitizing almost as potently as idebenone itself, explaining the persistent insulin sensitization of this rapidly metabolized molecule. These results help to identify key SAR = structure-activity relationship requirements for more potent small molecule Shc inhibitors as Shc-targeted insulin sensitizers for type 2 diabetes.